Heart Rate Variability in Patients with Hypertension: the Effect of Metabolic Syndrome and Antihypertensive Treatment - Małgorzata Maciorowska; Paweł Krzesiński; Robert Wierzbowski; Grzegorz Gielerak (Hindawi-Wiley, 2020)
Metabolic syndrome (MetS) is a combination of factors which, collectively, increase cardiovascular risk to a greater extent than each of them separately. Previous studies showed high cardiovascular risk to be associated with autonomic nervous system dysfunction. The purpose of this study was to assess the effects of antihypertensive treatment on heart rate variability (HRV) in patients with hypertension (HTN), depending on cooccurrence of MetS. 118 patients with uncontrolled HTN were enrolled to the study. HRV was compared among patients with and without MetS (MetS [+], n=70) at baseline and following 12 months antihypertensive treatment. The HRV indices measured from RR intervals recorded form using 24-hour ambulatory electrocardiography. The measured HRV domains were the standard deviation of the average of NN intervals [SDNN], square root of the mean of the sum of the squares of differences between adjacent NN intervals [rMSSD], percentage of NN50 [pNN50], low frequency [LF], high frequency [HF], total power of variance of all NN intervals [TP], and LF/HF ratio. Baseline parameters: SDNN, rMSSD, pNN50, and HF were significantly lower in the MetS[+] compared to the MetS[-] subgroup (p<0.05). After a 12-month antihypertensive treatment, MetS[+] patients achieved a significant improvement in parameters: SDNN, rMSSD, pNN50, and TP (p<0.05), while the changes in HRV observed in the MetS[-] subgroup were not statistically significant. The cooccurrence of HTN and other components of MetS is associated with disturbances of the autonomic balance. HTN control has a beneficial effect on HRV, with the effect being more evident in patients with MetS.